Induced tumor associated autoantibodies (iTAAs) by hapten plus drugs for targeting oncogenic nuclear antigens at sentinel lymph node of pancreatic cancer - Wang, Lei; Yu, Baofa; Zhang, Jian; Han, Yan; Zheng, Guoqin (Trends in Immunotherapy, 2024)
Background: the abscopal is a hypothesis of effect on non-irradiated tumors after localized radiation therapy which associated with the products of tumor-associated gene as autoantibodies (aTAAs) in reaction to the tumor-associated antigens (TAAs). When TAAs interact with hapten within tumor after hapten plus chemotherapy drugs intratumoral injection to pancreatic cancer like tumor lysates vaccine, TAAs-hapten stimulates the immune system as a neu antigen and produces autologous tumor antibodies, it is called induced tumor-associated autoantibodies (iTAAs) which is lightly difference to aTAAs since epitope of antigen linked with hapten. Method: immunofluorescence (IF) was applied for detect the binding of the iTAAs in tumor cells at sentinel lymph node. Results: aTAAS naturally could not target and bind the TAAs in tumor since due to immune tolerance. The iTAAs can target and bind the TAAS, also the iTAAs targeted in the tumors of sentinel lymph node with complements C help, it was found Cmyc (P = 0.0017 at one week; P = 0.0001 at two weeks), p53 (P = 0.0373; 29.13 ± 6.91, and P = 0.0254), and Zeta (P = 0.1513, P = 0.0044) increased significantly in the tumor cells or perinuclear tumor cells in lymph node at one and two weeks after treatment. Conversely, IMP1 (P = 0.6154; P = 0.0138), Koc (P = 0.5684, P = 0.0103), Survivn (P = 0.1020; P = 0.0147) and Rala (P = 0.3226; P = 0.0249) increased significantly in the cell or perinuclear of tumor in lymph node at two weeks later following. Conclusions: it indicated all of iTAAs plays a function in the binding of original cellular tumor genes at sentinel lymph node while the aTAAs could not bind the cellular tumor genes at lymph node due to immune tolerance. We could make a hypothesis: TAAs inside the cancer cells’ nuclei can be targeted by the iTAAs which produced by hapten enhanced intratumoral chemotherapy. The iTAA may play a distinctive role in controlling tumor cell growth and resulting in an abscopal effect, which is one of hapten associated with TAA induced immune response.